Novel silaproline (Sip)-incorporated close structural mimics of potent antidepressant peptide drug rapastinel (GLYX-13) - Madica, Krishnaprasad; Nadimpally, Krishna Chaitanya; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2017)
Rapastinel (GLYX-13) is a C-amidated tetrapeptide drug under clinical development for adjunctive treatment of major depressive disorder (MDD). Rapastinel features two consecutive proline residues centered at the peptide sequence (Thr-Pro-Pro-Thr-NH2), which are detrimental to its biological activity. In this communication, we report the synthesis of very close structural analogues of rapastinel comprising silaproline (Sip) as proline surrogate. By virtue of its enhanced lipophilicity and metabolic stability, Sip introduction in the native rapastinel sequence is expected to improve its pharmacokinetic profiles.

Rigid peptide scaffold-incorporated structural analogs of the potent antidepressant peptide drug rapastinel (GLYX-13) - Nadimpally, Krishna Chaitanya; Chakrapani, Aswathi; Prabhu, Priyanka J.; Madica, Krishnaprasad; Sanjayan, Gangadhar J. (Chemistryselect, 2017)
Rapastinel (GLYX-13) is a natural amidated tetrapeptide (Thr-Pro-Pro-Thr-NH2)endowed with strong antidepressant property. Rapastinel shows considerable promise for treating drug-resistant major depressive disorder (MDD), and is under clinical phase III development. Herein, we report the synthesis of a novel class of analogues of the potent antidepressant peptide drug rapastinel featuring rigid dipeptide scaffolds comprising proline (L/D) and amino thiophene carboxylates (Atc). Amino thiophene carboxylate is a conformationally constrained aromatic beta-amino acid, known to rigidify peptide backbones thereby limiting the conformational flexibility of peptides and improving proteolytic stability.

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template

Synthesis of hexaphenylbenzene-based template assembled synthetic proteins - Madhu, Suresh; Madica, Krishnaprasad; Gonnade, Rajesh; Sanjayan, Gangadhar J (Tetrahedron Letters, 2019)
Template-assembled synthetic proteins (TASPs) synthesized from rigid templates have attracted attention due to their interesting structural architectures and potential biomedical applications. Herein, we report the design, synthesis and characterizations of TASPs based on hexaphenylbenzene template (HPB) having twelve peptide attachable axial-arms in its structure. The peptides were attached to all the axial-arms of the template in a single step using simple solution phase peptide coupling strategy. The reaction conditions were standardized systematically using simple amines from smaller size to larger ones. (C) 2019 Elsevier Ltd. All rights reserved.

N-heterocyclic carbene catalysis exploiting oxidative imine umpolung for the generation of imidoyl azoliums - Das, Tamal Kanti; Madica, Krishnaprasad; Krishnan, Jagadeesh; Marelli, Udaya Kiran; Biju, Akkattu T. (Journal of Organic Chemistry, 2020)
Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cyclization and preliminary mechanistic experiments are also provided.